New perspectives on the development of communicative and related competence in foreign language education - Walker, Izumi; Chan, Daniel Kwang Guan; Nagami, Masanori, 1974-; Bourguignon, Claire (Trends in applied linguistics ;, 2018)
"This book offers insights from current research on the development of knowledge, skills and competencies in language teaching and learning and in second/foreign language acquisition. It presents theoretical frameworks and new perspectives by leading scholars that bear important implications for language education. It also discusses innovative and practical approaches for the teaching and learning of languages"--